1987
DOI: 10.1159/000284487
|View full text |Cite
|
Sign up to set email alerts
|

Dysphoric States in the Course of Manic-Depressive Illness

Abstract: The purpose of the present study is to investigate the relationship between dysphoric states (episodes in which irritable mood is prominent and relatively persistent) and manic-depressive illness. A further purpose is to clarify the probable causal influence of chemotherapy and the social consequences concerning dysphoria. The observations carried out on 14 patients are illustrated by 2 case reports. A strong tie seems to exist between dysphoric state and manic-depressive illness, especially with respect to ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…Some studies of dysphoric mood in bipolar disorder and delusional disorder have shown a high intraepisodic and interepisodic stability of dysphoric states [40, 41]. Such studies have provided the empirical basis for the proposal by Viennese psychopathologists of a tripolar classification of affective disorders, where dysphoria is seen as a third mood quality separated from depression and mania, and there is a dysphoric axial syndrome besides a depressive and a manic axial syndrome [42].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies of dysphoric mood in bipolar disorder and delusional disorder have shown a high intraepisodic and interepisodic stability of dysphoric states [40, 41]. Such studies have provided the empirical basis for the proposal by Viennese psychopathologists of a tripolar classification of affective disorders, where dysphoria is seen as a third mood quality separated from depression and mania, and there is a dysphoric axial syndrome besides a depressive and a manic axial syndrome [42].…”
Section: Discussionmentioning
confidence: 99%
“…It was also possible to show that dysphoric states might occur as separate episodes in the context of affective psychoses. The classical manic depressive disorder therefore can no longer be considered as a bipolar but as a tripolar disorder [14].…”
Section: Dysphoria In Contemporary Classificationmentioning
confidence: 99%
“…Treating dysphoria like an orphan, however, completely contradicts the importance it may have for the individual patient. Former studies have shown that certain effects of dysphoric syndromes (especially when they are not recognized as pathological phenomena) may have fatal consequences for the person suffering from them [14]. Far from being an untreatable personal characteristic, it has been shown repeatedly in recent years that in many cases dysphoria is a psychiatric disorder which can be treated psychopharmacologically [16][17][18][19][20][21].…”
Section: Dysphoria In Contemporary Classificationmentioning
confidence: 99%
“…The present volume takes up the issue raised by the Vienna School 15 years ago and widens its scope, addressing seriously the hope expressed by Musalek et al [6]: 'Whether further studies in this field should be undertaken, it cannot be merely a question of scientific interest; it is above all a question of humanity'. In fact, not only the connection between psychopathological assessment and nosographical concerns is at issue in this monograph, but also (and mainly) it is the humanity connection of the discourse on dysphoria that we elaborate here.…”
mentioning
confidence: 97%
“…These findings are taken as indicators of the nosographi-Stanghellini cal distinction between the dysphoric syndrome and depression and mania [6,7], as well as being emblematic of the tripolarity of affective disorders.…”
mentioning
confidence: 99%